A method for in vivo evaluation of α-glucosidase inhibition using Drosophila - Nattapong Wongchum; Alongklod Tanomtong; Somchai Pinlaor; Chatmongkon Suwannapoom; Ananya Dechakhamphu (MethodsX, 2023)
The development of α-glucosidase inhibitors is essential for the prevention of type II diabetes. Previous research has investigated in vitro inhibition using isolated α-glucosidase, which may not accurately reflect physical processes. The method presented in this study aims to establish a rapid and inexpensive in vivo method to study the inhibition of α-glucosidase activity using Drosophila as a model organism. This method can be used to calculate the IC50 value of compounds of interest for inhibition of α-glucosidase activity. The method established in this study can be used for in vivo screening of anti-diabetic compounds. • A rapid and inexpensive in vivo method to study the inhibition of α-glucosidase activity. • This method can be used to calculate the IC50 value of compounds of interest for inhibition of α-glucosidase activity. • This is a useful method for in vivo screening of anti-diabetic compounds.